Implementasi Keadilan Restoratif dalam Tindak Pidana Perpajakan yang Dilakukan Wajib Pajak di Indonesia - Haris Saputra; Nursyamsuddin (Syntax Idea)
Taxes constitute a crucial source of national income, providing the necessary funds for state expenditures. Virtually every country in the world levies taxes on its citizens. The extent of tax collection depends on each country's policies in managing its finances and economy. Article 23 of the 1945 Constitution of Indonesia stipulates that "Taxes and other compulsory levies for state purposes are regulated by law." In this research, a normative juridical approach was employed, utilizing a statutory approach to analyze and assess legal regulations related to the researched issue, or employing legislation and regulations as secondary legal sources. Based on the research findings, the author concludes that in Indonesia, the legal provisions regarding tax offenses are governed by Law No. 28 of 2007 and Law No. 7 of 2021, as well as Minister of Finance Regulation No. 130/PMK.03/2009, which emphasizes collective benefits, particularly in the interest of the people's welfare and the state's revenue.